HISTORICAL NORMS IN THE NOVEL SHARKS, IDO, HOMA BY Y.B. MANGUNWIJAYA - Royani, Royani (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
This study aims to reveal the historical norm in Y.B. Mangunwijaya’s novel Ikan-ikan Hiu, Ido, Homa using a qualitative method. The primary data consist of the novel Ikan-ikan Hiu, Ido, Homa, while secondary data include books, journals, and articles related to historical norm. The analysis was carried out through intensive reading and interpretation of the text’s empty spaces (leerstellen) to identify the relation between reality and fiction. The findings show that the novel presents historical norms related to the Ternate Kingdom and its relations with other North Maluku kingdoms, the arrival of foreign powers (Portuguese and Dutch), and the Banda massacre. By reconstructing these elements, Mangunwijaya creates a humanistic reflection and a critique of power. The novel thus serves as a dialogic space between text and reality, between history and human consciousness.